2017
DOI: 10.3389/fmars.2017.00282
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Apples to Oranges: Common Trends and Thresholds in Anthropogenic and Environmental Pressures across Multiple Marine Ecosystems

Abstract: Ecosystem-based management (EBM) in marine ecosystems considers impacts caused by complex interactions between environmental and anthropogenic pressures (i.e., oceanographic, climatic, socio-economic) and marine communities. EBM depends, in part, on ecological indicators that facilitate understanding of inherent properties and the dynamics of pressures within marine communities. Thresholds of ecological indicators delineate ecosystem status because they represent points at which a small increase in one or many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 129 publications
0
35
0
Order By: Relevance
“…These include tracking ratios such as the exploitation index (landings to biomass), areal landings, landings to productivity, total revenue relative to biomass, revenue relative to productivity, and total employments relative to biomass; and ensuring that they do not fall below specific thresholds (c.f., Mace 1994;Botsford et al 1997;Murawski 2000;Horan et al 2011;McClanahan et al 2011;Large et al 2013Large et al , 2015. For example, Samhouri et al (2010), Large et al (2015) and Tam et al (2017a) showed for multiple systems that an exploitation index above 15% represented a threshold not to be exceeded, which had resulted in a tipping point in ecosystem status. Our findings show that exploitation rates for the Gulf of Mexico have approached or exceeded 15% and have remained closer to 10% for the Mid-Atlantic and New England regions.…”
Section: Integration Of Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…These include tracking ratios such as the exploitation index (landings to biomass), areal landings, landings to productivity, total revenue relative to biomass, revenue relative to productivity, and total employments relative to biomass; and ensuring that they do not fall below specific thresholds (c.f., Mace 1994;Botsford et al 1997;Murawski 2000;Horan et al 2011;McClanahan et al 2011;Large et al 2013Large et al , 2015. For example, Samhouri et al (2010), Large et al (2015) and Tam et al (2017a) showed for multiple systems that an exploitation index above 15% represented a threshold not to be exceeded, which had resulted in a tipping point in ecosystem status. Our findings show that exploitation rates for the Gulf of Mexico have approached or exceeded 15% and have remained closer to 10% for the Mid-Atlantic and New England regions.…”
Section: Integration Of Informationmentioning
confidence: 99%
“…Comparative marine ecosystem studies have high value (Vasconcellos et al 1997;Hunt and Megrey 2005;Megrey et al 2009;Murawski et al 2009). By comparing consistent, common data across systems, clear patterns can and have emerged (Link et al 2012;Murphy et al 2013;Tam et al 2017a). Furthermore, lessons learned from structured case study analysis can highlight strengths and successes, and conditions thereof, warranting application elsewhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigate the nature of the faunal responses to environmental gradients and determine the extent to which these gradients predict their distribution. Quantifying the shape and magnitude of organisms’ responses allows us to identify community thresholds when a small change in a gradient causes sharp increases or decreases in the occurrence of a range of different types of organisms (Connell et al, 2017; Groffman et al, 2006; Tam et al, 2017). These threshold responses are often exacerbated by species interactions, where the loss or gain of one or more key species may precipitate the loss or appearance of others (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant need for a framework like the one proposed here. Largely because we need to change the mindset when approaching fisheries issues from one of weighing or exploring every potential, optimized outcome to one of identifying workable solutions in the context of such oceanographic, ecological and socioeconomic complexity (Boyd, Lennartz, Glover, & Doney, 2015;Cheung et al, 2010;Fulton et al, 2019;Halpern et al, 2015Halpern et al, , 2008Hilborn, 2011;Hoegh-Guldberg & Bruno, 2010;Jackson et al, 2001;Link, 2018;Link et al, 2012aLink et al, , 2012bLink & Marshak, 2019;Marshall et al, 2017;Micheli, Leo, Butner, Martone, & Shester, 2014;Ruckelshaus, Klinger, Knowlton, & DeMaster, 2008;Tam et al, 2017). We propose the first ever framework to systematically, simultaneously, comparatively and relatively explore population diagnostics that link responses to main causal factors.…”
Section: Discussionmentioning
confidence: 99%